SMOKING CESSATION IN A COMMUNITY PHARMACY: PRELIMINARY RESULTS OF A PHARMACEUTICAL CARE PROGRAMME - Condinho, Monica (2015)
Background: According to the World Health Organisation, tobacco use is one of the most widespread public health threats in the world, making it particularly urgent to promote smoking cessation. The ef- fectiveness of pharmacist interventions in smoking cessation has been documented in the international literature, but not sufficiently in Portugal. Objective: To report the preliminary results of study to assess the effectiveness of a smoking cessation programme delivered in Portuguese community pharmacies using an outsorcing-based regimen. Methods: Within the scope of a pharmaceutical care programme implemented in seven community pharmacies by an outsourced pharmacist, a specific consultation for smoking cessation was developed, in accordance with Portugal’s General Directorate of Health’s recommendations and instruments. The smokers were identified and invited to join the programme by the pharmacy staff during their daily activities. Patients that accepted signed an informed consent. Through several face-to-face and phone consultations and based on a comprehensive patient approach, personalised plans to quit tobacco were defined with the patients’ agreement. The effectiveness of the service was assessed through the evaluation of quit rates at 1, 6 and 12 months. The continuous variables were expressed as mean ± standard error of the mean. Results: During approximately 5 years (between January 2009 and July 2014), 69 smokers joined the programme. Of these, 17 desisted during the first consultation. Of the remaining 52 patients, the mean age was 47.4 ± 2.11 years old and 55.8% were male. A total of 264 pharmaceutical consultations were delivered and, on average, each patient received 7.7 ± 0.81 interventions. Most interventions (60.1%) were pharmacological (e.g. nicotine replacement products), while non-pharmacological measures (e.g. motivational interviewing) represented 39.9%. Five patients were referred to a physician. At 1 month after the quit date, 37 patients were abstinent (53.6%); 6 months later the number reduced to 24 (34.8%) and, 1 year later, 16 patients remained abstinent (23.2%). Conclusions: The implementation of a smoking cessation programme in community pharmacies using an external pharmacist may contribute effectively to tobacco cessation in Portugal.